2004
DOI: 10.1038/sj.ejhg.5201198
|View full text |Cite
|
Sign up to set email alerts
|

Three Rett patients with both MECP2 mutation and 15q11–13 rearrangements

Abstract: Autism and Rett syndrome, a severe neurological disorder with autistic behavior, are classified as separate disorders on clinical and etiological ground. Rett syndrome is a monogenic X-linked dominant condition due to de novo mutations in the MECP2 gene, whereas autism is a neurodevelopmental and behavioral disorder with complex genetic basis. Maternally inherited duplications on 15q11-q13 are found in a fraction of autistic children suggesting that an abnormal dosage of gene(s) within this region might cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
1
6
0
1
Order By: Relevance
“…Although rare, MECP2 mutations have been reported in individuals clinically diagnosed with AS or autism (56,57), and MECP2 mutations combined with rearrangements in 15q11-13 have been reported in individuals with RTT (58). In this study we show that GABRB3, a 15q11-13 gene, is positively regulated by MeCP2 and significantly reduced in both RTT and AS.…”
Section: Discussionsupporting
confidence: 52%
“…Although rare, MECP2 mutations have been reported in individuals clinically diagnosed with AS or autism (56,57), and MECP2 mutations combined with rearrangements in 15q11-13 have been reported in individuals with RTT (58). In this study we show that GABRB3, a 15q11-13 gene, is positively regulated by MeCP2 and significantly reduced in both RTT and AS.…”
Section: Discussionsupporting
confidence: 52%
“…Additional genetic alterations have been associated with the RTT phenotype, even in patients with a typical MeCP2 mutation. Longo et al 21 recently reported three patients with Rett syndrome and rearrangements of chromosome 15q11-13, a region known to be implicated in autistic phenotypes. 21 This suggests the possibility of the role of additional genes with the RTT phenotype, although further studies are necessary to confirm this association.…”
Section: Discussionmentioning
confidence: 99%
“…Longo et al 21 recently reported three patients with Rett syndrome and rearrangements of chromosome 15q11-13, a region known to be implicated in autistic phenotypes. 21 This suggests the possibility of the role of additional genes with the RTT phenotype, although further studies are necessary to confirm this association. Indeed, in a recent review of Weaving et al 22 , at least seven published atypical RTT cases have been found to have mutation in the Xlinked CDKL5/STK9 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation Specific PCR (MSPCR) analysis of SNRPN on DNA treated with sodium bisulfate (EZ DNA Methylation-Gold™) was performed (Kitsiou-Tzeli et al, 2010). In order to determine the parental origin of the 15q11.2 deletion (case 4), microsatellite markers D15S6A and nt5898 (Longo et al, 2004;Buiting et al, 2007) were studied on DNA from the patient and her parents by PCR and fragment analysis.…”
Section: Dna Methylation Analysis and Microsatellite Analysis For Thementioning
confidence: 99%